2019
DOI: 10.21276/aan.2019.4.2.56
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Haemodynamic Response to Conventional Tracheal Extubation and Removal of Classic Laryngeal Mask Airway (LMA-Classic) Following Bailey Manoeuvre: A Randomized Controlled Study

Abstract: Background: Exchanging endotracheal tube with laryngeal mask airway (LMA) before emergence from anaesthesia is one of the methods employed for attenuation of pressor response at extubation. We decided to compare the placement of Classic LMA (CLMA) before endotracheal extubation versus conventional endotracheal extubation in ASA I patients scheduled for elective surgeries under general anaesthesia. Subjects and Methods: 100 consenting adult patients were randomly allocated to two groups of fifty each; Group GET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The studies conducted by Suppiah et al, 21 and Kathor et al, 22 were observed similar finding as present study.…”
Section: Discussionsupporting
confidence: 91%
“…The studies conducted by Suppiah et al, 21 and Kathor et al, 22 were observed similar finding as present study.…”
Section: Discussionsupporting
confidence: 91%